Hosting Files Using Android Web Server (International Journal of Engineering and Computer Science, 2014)
Android is software platform and operating system for mobile devices. Being an open-source, it is based on the Linux kernel. It was developed by Google and later the Open Handset Alliance (OHA). It allows writing managed code in the Java language. Due to Android here is the possibility to write applications in other languages and compiling it to ARM native code. In this paper  a mobile-based web server was introduced for serving static HTML/JavaScript pages to the client systems (the systems could be PCs or Mobiles) for access by these client systems. A static website will be designed to serve from the mobile (web server). The Mobile Web server is based on Android OS. The static website saved inside the SD Card of the Android Mobile would be the source for the web server, thereby increasing the capability of the Mobile to become a web server for even PCs in the Network created by Android Mobile itself.